IMPROVING THE STUDENTS’ MATHEMATICS LEARNING OUTCOMES THROUGHQUANTUM TEACHINGMETHOD - Andi Mariani Ramlan (USN Kolaka, 2017)
As educators must be professional in choosing strategies, learning methods and techniques in directing competent students, especially learning mathematics. Maximizing learning activities as one of the efforts of educators by using one of the learning methods as a tool to achieve the planned learning objectives, so that all the potentials of students in the end can optimize the results of learning mathematics. The formulation of the problem in this research is